Generalization of One Sufficient Condition for Fourier Multipliers - Kolomoitsev, Yu. S. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We obtain new sufficient conditions for Fourier multipliers in the Hardy spaces H_p(R^n), 0 < p < 2. These conditions are given in terms of the simultaneous behavior of a function and its derivatives. The results of this paper generalize the corresponding theorems of A. Miachi.